Vibriocidal Titer and Protection From Cholera in Children. (11th February 2019) - Ritter, Alaina S; Chowdhury, Fahima; Franke, Molly F; Becker, Rachel L; Bhuiyan, Taufiqur R; Khan, Ashraful I; Saha, Nirod Chandra; Ryan, Edward T; Calderwood, Stephen B; LaRocque, Regina C; Harris, Jason B; Qadri, Firdausi; et al.
Abstract: Background: Vibrio cholerae, the causative agent of cholera, is a major cause of diarrhea worldwide. Children under the age of 5 have the highest disease burden of cholera. Vibriocidal antibody responses following natural infection and oral cholera vaccination (OCV) are associated with protective immunity, but whether this holds uniformly true in young children is not known. Methods: Household contacts of cholera patients are at high risk of V cholerae infection. We measured the association between baseline vibriocidal titer and the subsequent risk of infection in 50 household contacts <5 years old, 228 contacts 5–15 years old, and 548 contacts 16–70 years old in Bangladesh to determine whether vibriocidal antibody responses predict protection from V cholerae infection equally in all age groups. Results: We found that the vibriocidal titer predicted protection similarly in young children and other age strata. There was no interaction between age and vibriocidal titer. Mean baseline serum vibriocidal titers were higher in individuals in all age groups who remained uninfected compared with those who developed V cholerae infection during the follow-up period. Conclusions: After OCV, children have comparable vibriocidal responses to adults but a shorter duration and magnitude of protection compared with adults. In persons exposed to natural infection, we found that the vibriocidal titer predicts protection uniformly in all age groups. The vibriocidal titer may not be the optimal marker to demonstrate protection after OCV, and improved markers for estimating OCV efficacy in children are needed.